Depression mediated sleep disturbances and cognitive decline in Parkinson’s disease patient - Zhao, Huashuo; Sun, Yi; Wang, Qiushuang; Li, Sizhao; Zhao, Zixuan (Frontiers in Neuroscience, 2026)
ObjectiveThis study investigated the distinct mechanistic pathways linking depression, sleep disturbances, and cognitive decline in Parkinson’s disease, with emphasis on differential roles of daytime sleepiness versus rapid eye movement sleep disorder.ParticipantsThe study included 450 Parkinson’s disease patients enrolled in the Parkinson’s Progression Markers Initiative (PPMI) between 2010 and 2024, leveraging longitudinal clinical and biomarker data.MeasurementsDepressive symptoms (Geriatric Depression Scale, GDS), sleep disturbances (Epworth Sleepiness Scale, ESS for daytime sleepiness; REM Sleep Behavior Disorder Questionnaire, RBDSQ), and cognition (Montreal Cognitive Assessment, MoCA) were analyzed using mixed-effects models and structural equation modeling (SEM) with bootstrapped mediation.ResultsStructural equation modeling demonstrated excellent model fit (CFI/TLI > 0.94; RMSEA < 0.08). Analyses revealed distinct pathological pathways: (1) Excessive daytime sleepiness impaired cognition fully through depression mediation (indirect effect β = −0.084, 95%CI [−0.097,-0.028], 66.1% mediated), while (2) REM sleep behavior disorder showed both direct negative effects on cognition (β = −0.116, p = 0.035) and depression-mediated effects (indirect effect β = −0.071, 95%CI [−0.110,-0.029], 38.2% mediated). These results highlight different intervention targets - treating depressive symptoms may fully mitigate cognitive impacts of daytime hypersomnia, while RBD may require both antidepressant and direct neuroprotective approaches.ConclusionDivergent neurobehavioral mechanisms underlie sleep-related cognitive decline in PD: daytime sleepiness operates through mood dysregulation, while rapid eye movement sleep disorder involves additional direct neural insult. Interventions targeting these pathways may require distinct strategies.